Species Identification and Mycotoxigenic Potential of Aspergillus Section Flavi Isolated from Maize Marketed in the Metropolitan Region of Asunción, Paraguay - Juliana Moura-Mendes; Cinthia C. Cazal-Martínez; Cinthia Rojas; Francisco Ferreira; Pastor Pérez-Estigarribia; Nathalia Dias; Patrício Godoy; Jéssica Costa; Cledir Santos; Andrea Arrua (Microorganisms, 2023)
Zea mays var. amylacea and Zea mays var. indurata are maize ecotypes from Paraguay. Aspergillus section Flavi is the main spoilage fungus of maize under storage conditions. Due to its large intraspecific genetic variability, the accurate identification of this fungal taxonomic group is difficult. In the present study, potential mycotoxigenic strains of Aspergillus section Flavi isolated from Z. mays var. indurata and Z. mays var. amylacea that are marketed in the metropolitan region of Asunción were identified by a polyphasic approach. Based on morphological characters, 211 isolates were confirmed to belong to Aspergillus section Flavi. A subset of 92 strains was identified as Aspergillus flavus by mass spectrometry MALDI-TOF and the strains were classified by MALDI-TOF MS into chemotypes based on their aflatoxins and cyclopiazonic acid production. According to the partial sequencing of ITS and CaM genes, a representative subset of 38 A. flavus strains was confirmed. Overall, 75 A. flavus strains (86%) were characterized as producers of aflatoxins. The co-occurrence of at least two mycotoxins (AF/ZEA, FUM/ZEA, and AF/ZEA/FUM) was detected for five of the Z. mays samples (63%). Considering the high mycological bioburden and mycotoxin contamination, maize marketed in the metropolitan region of Asunción constitutes a potential risk to food safety and public health and requires control measures.